Устройство для возбуждения колебаний вала двухфазного асинхронного двигателя - Аристов А. В. Анатолий Владимирович; Шутов Е. А. Евгений Алексеевич; Малафиенко С. Г.; Федотов В. М.
опубл. 07.01.89, Бюл. № 1